Multimodal Discourse Analysis of Image-Biblical Verses - et.al, Prof. Riyadh Tariq Kadhim Al-Ameedi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study is about a text and an image that are combined together. These two parts work hand in hand to form a number of messages . The separation between them seems almost inextricable when it comes to the matter of making more effective messages . Therefore , the study focuses on this point to shed light on the linguistic relations between these parts. The texts to be analyzed are some biblical verses that are put in images . The study arrived at the results that multimodal discourse analysis plays a key role in a combination of verbal and non-verbal parts . These two parts have been represented by language and the components of the image like colours , the movement of certain things , the way the image is designed and so on . The study adopts the model of Kress ( 2010) ,Paltridge (2012), and Van Leeuwen(2005).